2023
DOI: 10.1542/peds.2023-062923
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Organ Donation and Transplantation: Across the Care Continuum

Abstract: This policy statement aims to enhance comfort and increase knowledge of pediatric organ donation and transplantation to the general pediatric community, specifically focusing on the pediatric health care professional and the medical home. The pediatric health care professional will care for neonates, infants, children, and adolescents who may become donors or transplant recipients and, thus, is a crucial member of the pediatric patient’s care team. Understanding donation, transplantation, and follow-up care ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Previous studies found that positive beliefs and attitudes of HCPs toward pDCDD are influenced by, and significantly correlate with, their knowledge about the processes, and that their comfort increases after an educational intervention [11, 19]. When faced with the second scenario, with donation failing due to the prolongation of the agonic time, around 30% of individuals surveyed declared that a failed donation could demotivate them in handling the request of future families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that positive beliefs and attitudes of HCPs toward pDCDD are influenced by, and significantly correlate with, their knowledge about the processes, and that their comfort increases after an educational intervention [11, 19]. When faced with the second scenario, with donation failing due to the prolongation of the agonic time, around 30% of individuals surveyed declared that a failed donation could demotivate them in handling the request of future families.…”
Section: Discussionmentioning
confidence: 99%
“…This finding confirms that pDCDD is a viable option for Italy, even if the Italian law requires a 20‐min no‐touch period to declare death based on cardiocirculatory criteria. This is the longest no‐touch period if compared to the 5 min of asystole in the United Kingdom or the 2 min of respiratory and circulatory function cessation in the United States [11]. The inclusion of this long no‐touch period in the functional warm ischemia time (fWIT) forces the Italian system to apply the extracorporeal regional perfusion on patients, a technique proven to be effective in restoring cellular metabolism [12] but requiring a significant economic and organizational effort [13].…”
Section: Introductionmentioning
confidence: 99%
“…4 The WBDP's description of the challenges associated with objections to BD/DNC and the recommendations to manage these objections has been cited in a few other publications. [200][201][202] A neurocritical care unit quality improvement caseworker cultural mediator project in Washington included mention of the WBDP's recommendations on this topic, as did a review for palliative care specialists on their role in managing requests for indefinite accommodation. 201,202 New Publications Related to Requests to Forego a BD/DNC Evaluation or Continue Somatic Support after BD/DNC Studies in the United States and Canada published after the WDBP demonstrated similar findings compared with prior surveys of physicians in the United States about their experience with requests to forego a BD/DNC evaluation or continue somatic support after BD/DC (approximately 50% An Update on BD/DNC since the World Brain Death Project Lewis of physicians involved in BD/DNC determination have received at least one such request).…”
Section: Background and Wbdp Recommendationsmentioning
confidence: 99%
“…The WBDP's description of the challenges associated with objections to BD/DNC and the recommendations to manage these objections has been cited in a few other publications. 200 201 202 A neurocritical care unit quality improvement caseworker cultural mediator project in Washington included mention of the WBDP's recommendations on this topic, as did a review for palliative care specialists on their role in managing requests for indefinite accommodation. 201 202…”
Section: Review Of the Wbdp And Updates Since Publicationmentioning
confidence: 99%